Associação entre as barreiras na implantação de sistemas de gestão da qualidade e os princípios da qualidade - Voltz, Cleiton Ismael (Universidade do Vale do Rio dos Sinos, 2018)
The main objective of this work is to identify the association between the barriers encountered in the implantation of quality management systems and the failures to understand the guiding principles of quality management. For that, a multiple case study was carried out in the footwear industry and supplies. As a way of assigning the desired associations, interviews and content and correspondence analyzes were carried out. The content analysis presented evidence of relation between several barriers cited in the literature and validated by managers, with failures in understanding the principles of quality. The correspondence analysis corroborated these indications, and it is possible to draw up an adequate plan to minimize failures in the implantation of a quality management system, in relation to previously encountered barriers. The contribution of this work is mainly to aggregate the existing discussions in the literature, suggestions of association between barriers in the implantation of a quality management system and principles of quality. Thus, when implanted in practice, quality managers will be able to identify potential barriers in the profile of their employees, and minimize them from a proper understanding of the principles during the training phase.
Keywords: ISO 9001:2015; Sistemas de gestão da qualidade; Barreiras; Princípios da qualidade; ISO 9001:2015; Quality principles; Quality management system; Barriers; ACCNPQ::Engenharias::Engenharia de Produção